UTILIZATION OF OPERATING SYSTEM IN 1 COMPUTER IN VIETUAL WITH VMWARE - Untung Wahyudi (Jurnal Sistem Komputer, 2008)
Platform GNU / Linux and the growing popular in the community have proven to provide many alternative solutions that drive efficiency and be more user friendly. Creating a virtual operating system can be easy, we can determine the installation and existing applications on the main operating system and guest operating systems. Making this virtual operating systems to illustrate some important points which are able to learn and provide flexibility. It also outlines the processes of how to install operating systems and applications.